Mandeh Special Economic Area (Kek) as The Model of Sharia Tourism Development in West Sumatra Province - Ansharullah Ansharullah; Harum Natasha (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2020)
This study is entitled